2019
DOI: 10.1097/won.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Training Needs of Staff Nurses Caring for Patients With Intestinal Ostomies in Primary and Secondary Hospitals in China

Abstract: PURPOSE: The purpose of this study was to describe staff nurses' intestinal ostomy care practice in primary and secondary hospitals in China and their ostomy-related training needs. SUBJECTS AND SETTING: The target population for this study was first-line staff nurses working in general surgical departments in primary and secondary care hospitals in Luzhou, located in Sichuan Province, Southwest China. Hospitals in China are divided into 3 tiers; first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…This finding may be because senior nursing staff with many years' experience are often employed in management positions; thus, they have less direct contact with patients' ostomy care. 22 This study has documented that nurses gain more confidence in their knowledge and skill as they gain more years of clinical experience.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This finding may be because senior nursing staff with many years' experience are often employed in management positions; thus, they have less direct contact with patients' ostomy care. 22 This study has documented that nurses gain more confidence in their knowledge and skill as they gain more years of clinical experience.…”
Section: Discussionmentioning
confidence: 92%
“…Another study found that nurses in China with more than 26 years of experience and working in high practice positions had significantly lower scores in knowledge and skill of ostomy care than nurses in bedside care or those with 15–25 years of experience. This finding may be because senior nursing staff with many years’ experience are often employed in management positions; thus, they have less direct contact with patients’ ostomy care 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings by Cross and colleagues 8 also support that staff nurses without specialized ostomy education felt more confident in emptying the ostomy pouch as opposed to other ostomy care skills. Duruk and Uçar 9 in Turkey and Li and colleagues 10 in China also reveal that staff nurses lack adequate knowledge about the care of patients with ostomies. Better ostomy care outcomes have been reported when patients are cared for by nurses who have had specialized ostomy education.…”
Section: Educationmentioning
confidence: 99%